BELAJAR DARI KEUNGGULAN PENGELOLAAN PENDIDIKAN FINLANDIA DAN RELEVANSINYA DENGAN PEMIKIRAN KI HAJAR DEWANTARA TENTANG PENDIDIKAN - Hailitik, Hengky (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2024)
Abstract. Education plays an important role in the progress and development of a country. Finland as one of the countries with the best education system can be a reference for advancing education in Indonesia. Apart from that, the thoughts of educational figure Ki Hajar Dewantara through the formulation of educational theories which are embodied in Taman Siswa education can also be a reflection of learning to improve the quality of Indonesian education today. The purpose of writing this article is to explore the excellence of education in Finland and Ki Hajar Dewantara thoughts on education. The method used is literature study and descriptive analysis to explore the results of literature study exploration. The results obtained are that the excellence of education in Finland, among others, is the existence of principles of equality, equity, and diversity in education management. Furthermore, the decentralized system, varied curriculum, learning and assessment are other advantages of education in Finland. The last is related to teacher qualifications and competencies. Meanwhile, from Ki Hajar Dewantara thinking, 8 educational theory formulations were found, namely human nature theory, natural nature theory, basic and teaching theory, among theory, tricenter theory of education, free spirit education theory, independence theory, and complete learning theory. The integration of Finnish educational excellence and the concept of KHD thinking can be a good practice that can be implemented in order to improve the quality of Indonesian education. Abstrak. Pendidikan berperan penting pada kemajuan dan perkembangan suatu negara. Finlandia sebagai salah satu negara dengan sistem pendidikan terbaik dapat menjadi acuan untuk memajukan pendidikan di Indonesia. Disamping itu, pemikiran dari tokoh pendidikan Ki Hajar Dewantara melalui rumusan teori pendidikan yang terejawentahkan dalam pendidikan Taman Siswa juga dapat menjadi cerminan pembelajaran untuk meningkatkan kualitas pendidikan Indonesia saat ini. Tujuan penulisan artikel ini adalah mengeksplorasi keunggulan pendidikan di Finlandia dan pemikiran Ki Hajar Dewantara tentang pendidikan. Metode yang digunakan adalah studi literatur dan analisis deskriptif untu mendalami hasil eksplorasi studi literatur. Hasil yang diperoleh adalah keunggulan pendidikan di Finlandia antara lain adalah adanya prinsip equality, equity, dan diversity dalam pengelolaan pendidikan. Selanjutnya sistem desentralisasi, kurikulum, pembelajaran, dan penilaian yang variatif menjadi keunggulan lainnya pendidikan di Finlandia. Terakhir adalah terkait kualifikasi dan kompetensi guru. Sedangkan dari pemikiran Ki Hajar Dewantara ditemukan 8 rumusan teori pendidikan yaitu teori kodrati manusia, teori kodrat alam, teori dasar dan ajar, teori among, teori tripusat pendidikan, teori pendidikan jiwa merdeka, teori kemandirian, dan teori belajar tuntas. Integrasi keunggulan pendidikan Finlandia dan konsep pemikiran KHD dapat menjadi praktik baik yang dapat dimplementasi dalam rangka meningkatkan kualitas pendidikan Indonesia.